2018
DOI: 10.1002/ange.201806059
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Iron(III) Porphyrin‐Catalyzed Intramolecular C(sp3)–H Amination of Alkyl Azides

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
(17 reference statements)
0
8
0
Order By: Relevance
“… 52 The group of Che used an NHC-PorFe catalyst for the preparation of saturated nitrogen heterocycles from alkyl azides. 53 Recently, a highly functional group tolerant PcMn analogue was disclosed for intermolecular, benzylic C–H amination; multiple late-stage derivatizations of biologically active compounds were exemplified ( Scheme 3 A). 54 In parallel, the group of Zhang has led the development of the corresponding PorCo systems.…”
Section: Next Generation Metal Catalystsmentioning
confidence: 99%
“… 52 The group of Che used an NHC-PorFe catalyst for the preparation of saturated nitrogen heterocycles from alkyl azides. 53 Recently, a highly functional group tolerant PcMn analogue was disclosed for intermolecular, benzylic C–H amination; multiple late-stage derivatizations of biologically active compounds were exemplified ( Scheme 3 A). 54 In parallel, the group of Zhang has led the development of the corresponding PorCo systems.…”
Section: Next Generation Metal Catalystsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…Our synthesis ( Scheme 4 ) began with the preparation of 2-bromo-5-(but-1-en-1-yl)pyridine ( 4 ) from commercially available 6-bromonicotinaldehyde ( 5 ) and n -propyltriphenyl-phosphonium bromide by using the Wittig reaction [ 30 ], followed by a hydrogenation reaction [ 31 ] to afford 2-bromo-5-butylpyridine ( 3 ). Once 2-bromo-5-butylpyridine ( 3 ) was in hand, a carbonylation reaction [ 32 ] was carried out immediately and methyl 5-butylpicolinate ( 2 ) was obtained.…”
Section: Resultsmentioning
confidence: 99%